2022
DOI: 10.3389/fpsyg.2022.853371
|View full text |Cite
|
Sign up to set email alerts
|

Adhoc Setup of an Online Mental Health Self-Help Program During the COVID-19 Pandemic: Description of the Development and Implementation Processes and Analysis of Its Users’ and Usage Profiles

Abstract: BackgroundThe COVID-19 pandemic hit Austria in March 2020. This led to a considerable reduction in outpatient psychiatric therapies. People with mental disorders as well as with newly emerging mental health issues found themselves with very limited treatment options. Within only a few days our hospital set up an online mental health self-help program which went online in its first version on the first day of the lockdown in Austria. The process of this development and implementation process alongside with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…During the COVID‐19 pandemic, it became necessary to implement virtual self‐help due to increasing demand and limited availability of therapists. A recent study (Galffy et al, 2022) and systematic review (Fischer et al, 2020) for virtual self‐help found it to be effective for anxiety, depression and stress‐related conditions, but perhaps not as effective as face‐to‐face interventions. To our knowledge, this is the first study to examine the feasibility of a parental self‐help intervention, based on an adapted FBT model with no therapist involvement and provided to families on a waitlist for pediatric ED services during the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID‐19 pandemic, it became necessary to implement virtual self‐help due to increasing demand and limited availability of therapists. A recent study (Galffy et al, 2022) and systematic review (Fischer et al, 2020) for virtual self‐help found it to be effective for anxiety, depression and stress‐related conditions, but perhaps not as effective as face‐to‐face interventions. To our knowledge, this is the first study to examine the feasibility of a parental self‐help intervention, based on an adapted FBT model with no therapist involvement and provided to families on a waitlist for pediatric ED services during the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%